INTERBANK COMPETITION FOR ATTRACTING IDLE FUNDS OF LEGAL ENTITIES AND INDIVIDUALS - Rufat Bakhtiyorovich Kurbanov; Inomjonov Muslimjon Qaxramon ugli (American Journals, 2023)
The article describes measures taken by banks to attract funds from legal and natural persons, restrictions and privileges in providing deposits to the population, as well as the control of the activities of commercial banks in attracting deposits by the Central Bank, researches about laws and regulations will be covered.
Keywords: population savings, depositor, deposits, bank resources, deposit operations, commercial banks.